INFLUENCE OF LIGHT SPECTRUM AND BENZYLAMINO PURINE ON SOME VEGETATIVE AND CHEMICAL PROPERTIES OF SHOOTS ON TWO VARIETIES OF GERBERA JAMESONII IN VITRO - & Hamad, AL-Hamidawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was conducted at the plant tissue culture Lab.College of Agriclture, University of Baghdad from February to October 2015. The aims of the study were investigate the influence of light quality and Benzylamino purine ( BA) on some vegetative and chemical properties of shoots for two varieties Martinque and Yanara of Gerbera jamesonii . cultured on MS medium supplemented with 0.3 mg.L-1 NAA, 0.4 mg.L-1 Kinetin, 0.3 mg.L-1 Spermidine ,100 mg.L-1 Adenine sulphate. The highest number of shoots/explant ( 6.14 ) were When MS medium supplemented with 3 mg/L-1 of BA grown under red light with Martinque variety Which did not significantly differ than explants under White light ( 6 shoots/ explant ). The interaction between variety and kind of light indicated that on MS free medium gave the highest length of shoots (7.33 , 6.70 cm) for Martinque and Yanara respectively .Total Chlorophyll content of shoots was highest ( 33.37 SPAD) in cultures for Martinque variety illuminated with White light . The results showed that ( 36.36 SPAD) of total Chlorophyll content were achieved with MS medium modified with 3 mg/L-1 BA under White light conditions. The highest values of shoot fresh weight ( 776.4 mg) was reconded on explants illuminated with White light on the medium supplemented with 1.5 mg/L-1 BA for Yanara variety . While the MS medium supplemented with 3 mg/L-1 BA under White light gave the greatest dry weight ( 64.7 mg) for the Martinque variety which did not differ significantly from the Yanara variety (64.1mg). Higher percentage of Carbohydrates (24 %) was recorded under red light on (BA)-free medium for Martinque variety .